Clomipramine Misuse in a Patient with Schizophrenia - Ünler, Mehmet; Horaz, Ayşe (Addicta: The Turkish Journal on Addictions, 2023)
Although antidepressants are theoretically safe, the abuse of antidepressant drugs is increasingly taking place in the literature. Most cases had a history of concomitant alcohol or substance use. We present a 49-year-old female patient with a diagnosis of schizophrenia who had a clomipramine misuse history without alcohol or substance addiction. The patient gradually increased the clomipramine dose without the doctor’s advice. She used clomipramine in higher doses than usual and often requested the doctors to prescribe it to relieve her complaints. Patients with a history of psychotic illness may abuse anticholinergics to reduce existing anhedonia. Therefore, our patient may have used clomipramine to alleviate the anhedonia she experienced. Tricyclic antidepressant abuse can be fatal so it is important to recognize this phenomenon.
Keywords: Antidepressant abuse; antidepressant misuse; clomipramine; drug abuse; tricyclic antidepressants